Biocontrol Substances in Europe: A Slow Shift Towards Dominance - Marchand, Patrice A. (Chronicle of Bioresource Management, 2023)
Following our survey on biocontrol of active substances under the plant protection products (PPP) Regulation EC 1107/2009, we show a constant progression of the BioControl Agents (BCA) in Europe since 2011 up to actual 48% of the total active substances in EU. However, comments on these data and results exhibit a lack of the full qualification of this increase in amount, percentage, and percentage of increase, in the last twelve years.